Environment-Sensitive Nanofibers and Anchoring of Dyes - Ge, Liqin; Wang, Weichen; Yao, Chong; Xu, Zeying (Asian Journal of Chemistry, 2012)
In this paper a new type of multilayered hollow nanofibers was fabricated through the combination of the layer-by-layer technique and the electro-spinning method by removal of the template nanofibers. The morphology of the obtained nanofibers was observed when they were treated in different environments; i.e. different pH solutions and heating conditions. The ability to carry a dye in the obtained hollow multilayer nanofibers was probed and the result shows that the obtained nanofibers can anchor dyes effectively.